Highly sensitive refractive-index sensor based on strong magnetic resonance in metamaterials. (15th April 2019) - Chen, Jing; Nie, Hai; Tang, Chaojun; Cui, Yinhang; Yan, Bo; Zhang, Zhiyuan; Kong, Yurong; Xu, Zhijun; Cai, Pinggen
Abstract: We demonstrate a very strong magnetic resonance in metamaterials for high-performance sensing. The metamaterials comprise a periodic array of a pair of closely spaced metal nanodisks that are placed on metal substrate. The strong magnetic resonance is essentially an antisymmetric resonant mode resulting from the near-field plasmon hybridization within the pair of metal nanodisks. Because the magnetic resonance has great electromagnetic field enhancement, ultra-narrow bandwidth and nearly perfect absorption, the metamaterials have very high sensitivity ( S = 991 nm/RIU, S* = 47/RIU) and figure of merit (FOM = 124, FOM * = 17 702), which may find potential applications in label-free biosensing.